“The very air is a vital essence”: Pneumaticism at the Poles - Fulford, Tim (Romanticism and Victorianism on the Net, 2016)
I discuss the culture of accurate and dispassionate mensuration in an Arctic that was, for the first time, predictably attainable—a technologized Arctic near enough to be reached and subjected to experiment. My purpose is to develop, in the context of the discourse of polar exploration and the British responses to that discourse made by poets and fiction writers, recent arguments about the culture of scientific experiment and the so-called rise of “objectivity” that have been made by historians of science. The effect of these arguments has been to suggest that a mutually reinforcing objectification of experiment narrative and establishment of professional institutions set nineteenth century science apart from natural philosophy as practised by amateur eighteenth-century gentlemen—Erasmus Darwin being a typical gentleman of that kind.Here, I suggest that the extreme regions of the poles not only challenged the authority of accurate observation as a defining virtue of science from within the discourse of science, but also inspired fictional narratives that challenged it—and thus called the new science into question. Thus I reveal the effects, in literary texts and the wider culture as well as in expedition narratives and scientific discourse, when experiments did not produce predictable results, or failed completely to comprehend their subjects. I suggest that because of its simultaneous availability and resistance to investigation, the Arctic became an external representative of the fear and desire buried within scientific objectivity. It has remained fascinating in the European cultural imaginary for this reason, as an Other, embodying fear but also longing for a world that eludes mastery by our technologies of knowledge-production. A consequence of this is that aspects of the Arctic have been used by Europeans to configure alternatives and oppositions to scientific culture as it was practised from the early nineteenth century onwards. Specifically, “The Ancient Mariner” and Frankenstein interrogate the claims of “objective” report and accurate experiment and, in doing so, remodel Erasmus Darwin’s fictionalisation and poeticisation of scientific discourse for a more vexed and hostile literary context than the one in which he wrote